Cybersecurity Impact of Cybercrime in Strengthening Trust In BSI Kc Rantau Prapat - Zulfa Khoiriah; M. Ikhsan Harahap; Nursantri Yanti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The study aims to analyze the impact of cybercrime security in increasing customer confidence in bsi kc prapat region.This research uses a quantitative method with a case study approach. Data collected through questionnaires A new study was conducted to test the impact of cybercrime security on customer confidence, involving customers of Bank Syariah Indonesia (BSI) in the Prapat Region. Research results show that cybercrime security has a positive and significant impact on customer confidence, suggesting that customers have more confidence in banks that are able to secure their data from cyber crime threats.In conclusion, cybercrime security plays an important role in building andining customer confidence in the Shariah financial industry. Banks need to continue to improve their security infrastructure and respond quickly to security incidents to ensure customer confidence remains awake.